Antenatal-care knowledge among women of reproductive age group in Ido Ekiti, NigeriaAJOG Global Reports at a Glance - Damilola A. Jesuyajolu, MBBS; Peace Ehizibue, MBBS; I. Nnamdi Ekele, MBBS; Jamike Ekennia-Ebeh, MBBS; Abdulqudus Ibrahim, MBBS; Obinna Ikegwuonu, MBBS (Elsevier, 2022)
BACKGROUND: Maternal mortality plagues much of the low- and low-middle-income countries. There were 303,000 maternal deaths in 2015, representing an overall global maternal mortality ratio of 216 maternal deaths per 100,000 live births. 99% of all maternal deaths occur in developing countries. The knowledge of antenatal care is an important factor affecting maternal mortality rates. OBJECTIVE: This study aimed to assess the extent of knowledge of antenatal-care services among women of reproductive age in Ido Ekiti, a rural town in South West Nigeria. STUDY DESIGN: This cross-sectional study was conducted among 299 women in the reproductive age group, ie, from the ages of 18 to 49 years. Data were collected with a set of self-administered questionnaires and analyzed using SPSS version 25. This study was conducted in Ido Ekiti, a town in the Ido-Osi local government area. RESULTS: Most respondents were between 31 and 40 years of age. Most respondents (96%) were educated. 95.6% of the participants in this study were aware of antenatal-care services. 98.7% of the respondents acknowledged that weight and height measurements, abdominal examination, blood tests, and administration of folic acids were carried out during antenatal-care visits. 97.3% had excellent knowledge of the service. CONCLUSION: Most respondents were aware of antenatal care and had excellent knowledge of its components. This is indeed a positive finding and is likely because of the high literacy levels, access to electronic media, and the location of 3 public health facilities in the town. Continuous education of women by relevant stakeholders and policymakers on antenatal care should be ensured to maintain the current state and replicate similar findings in other rural areas across Africa.